Twinning-induced dislocation and coordinated deformation behavior of a high-Nb TiAl alloy during high-cycle fatigue - Xu, Xuesong (2023)
The deformation mechanism responsible for the high-cycle rotating bending fatigue of a high-Nb TiAl alloy was investigated. Fatigue deformation in the γ phase was dominated by superlattice dislocations [0 1 1¯] and twinning. Dislocations 〈1 1 0〉 in the B2 phase can be induced by twins in the adjacent γ phase, which has a low stacking fault energy owing to the high Nb content. Stress transfer between two adjacent phases can be accomplished through atomic rearrangement of the interface by twinning. The local stresses were accommodated by the continuous dislocation slip of the B2 phase, deformation twins, and twin intersections in the γ phase.